(untitled) (Research, Society and Development, 2020)
The present study aimed to identify in the literature the understanding, understanding and perception of mothers of newborns about the use of the kangaroo method. It is an integrative review type research. The search for the studies took place between March and April 2019 via VHL, SciELO and LILACS, conducted by the research question: “How does the maternal perception occur when using the kangaroo mother method in neonates?”. 14 articles were identified, in which 14.3% of publications prevailed between the years 2016, 2015, 2013 and 2003 (57.2%) and 7.1% between the years 2018, 2014, 2010, 2009, 2008 and 2007 (42.6%). After analysis, the results and information were divided into three categories: Sensations and expectations with the RNAs; Influence of the environment; and Improvement in the mother and child binomial. It was found that the Kangaroo Mother Method brings benefits to the health of low birth weight newborns, reduces the cost and length of hospital stay, humanizes care and improves the mother-child bond.